Final Basel III Modelling Implementation, Impact and Implications - Akkizidis, Ioannis (Springer International Publishing, 2018)
This book provides a concise and practical guidance on the implementation analysis of the new revised standards of the Basel Committee on Banking Supervision (BCBS) on the supervision of the international banking system. Based on publicly available data on default rates and realised loss-given-default rates, it provides an analysis of credit and market risk, assessing the extent to which the new framework on risk-based and leverage ratio requirements affects the modelling of banking risks. Moreover, it provides a detailed analysis of the Fundamental Review of the Trading Book (FRTB), which changes the philosophy for the risk valuation and capital requirements of the market risk, and of the latest developments on the credit valuation adjustments (CVA) framework. It also examines the impact of the final calibration of operational risk parameters on the level of capital requirements. It provides an overview of the modelling properties that govern the application of the internal models for credit and market risk, and provides evidence on the overall impact on banks' cost of funding due to the implementation of Basel reforms as shaped in December 2017. Finally, the book provides practical examples and hands-on applications for assessing the new BCBS framework.